2021
DOI: 10.1785/0120200386
|View full text |Cite
|
Sign up to set email alerts
|

Testing Nonlinear Amplification Factors of Ground-Motion Models

Abstract: We explore nonlinear site effects in the new Japanese ground-motion dataset compiled by Bahrampouri et al. (2020). Following the approach of Seyhan and Stewart (2014), we evaluate the decrease of soil amplification according to the increasing and corresponding ground motion on surface rock (VS30=760  m/s). To better predict the rock ground motion associated with each record, we take into account the between-event variability of the ground motion, and to better evaluate the impact of nonlinearity, we correct ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In particular, the non‐linear site response term in horizontal GMM was neglected because there are insufficient records to robustly constrain these effects. Another strategy, followed in several works (GA2011; AK2014; BC2016) consists in calibrating the non‐linear site scaling on the basis of numerical simulations; however, this approach tends to over‐estimate the effects of the non‐linearity, especially at short periods 44,45 …”
Section: Calibration Of the Ita18 Vh Modelmentioning
confidence: 99%
“…In particular, the non‐linear site response term in horizontal GMM was neglected because there are insufficient records to robustly constrain these effects. Another strategy, followed in several works (GA2011; AK2014; BC2016) consists in calibrating the non‐linear site scaling on the basis of numerical simulations; however, this approach tends to over‐estimate the effects of the non‐linearity, especially at short periods 44,45 …”
Section: Calibration Of the Ita18 Vh Modelmentioning
confidence: 99%
“…As shown in Figure 14, we supplemented a brief comparison between the HSAFs estimated using GMM performed by Loviknes et al., 44 Hybrid method 2, and GIT at five stations. Please note that the HSAFs by GMM released from them are originally the relative Fourier spectral amplification ratio with respect to the average spectra of all the sites as their GMM is referring to.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between the HSAFs estimated using GMM for the Fourier spectra performed by Loviknes et al., 44 Hybrid method 2, and GIT at (A) IBUH01, (B) KGWH03, (C) KGWH04, (D) SBSH09, and (E) TTRH07. At the top of each panel, we labeled the site name selected for Hybrid method 2…”
Section: Discussionmentioning
confidence: 99%
“…It is not obvious why the nonlinear site-response terms for Japanese sites behave differently from those of other regions. Several studies of individual KiK-net sites have shown that the nonlinear behavior of these sites is quite variable and not necessarily related to the value of V S 30 at the site, which is attributed to various factors, including (1) the averaging of the shear-wave velocity profile over the top 30 m, (2) the strong velocity impedance at shallow depths exhibited by many Japanese KiK-net sites, (3) the relatively shallow soft-soil layers of typical Japanese KiK-net sites, or (4) a combination of these effects (Bonilla et al, 2021; Ji et al, 2021; Loviknes et al, 2021; Zalachoris, 2014). We also note that the small V S 30 , large A 1100 recordings from our database come primarily from two earthquakes and that the number of recordings for the softest sites from these events are limited.…”
Section: Relationship Between Nonlinear Site Response and Rock Pgamentioning
confidence: 99%